Composite current collector welding method

By reserving the pole ear area on the composite fluid and punching holes, combining the coordination of conductive glue and through holes, and using an ultrasonic welding machine for welding, the problem of insufficient connectivity of the metal coating in composite fluid welding is solved, and efficient Conductivity and yield.

CN119447724APending Publication Date: 2025-02-14JIANGYIN NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411621755.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the existing composite fluid collecting welding technology, the connectivity of the metal plating between the composite fluid collecting during ultrasonic welding is insufficient, resulting in an increase in internal resistance and affecting current conduction.

Method used

By reserved pole ear zones on the composite fluid collection and drilling holes, combining the coordination of conductive glue and through holes, welding is improved by using an ultrasonic welding machine.

Benefits of technology

This method reduces the waste of materials in roller welding, simplifies the process, realizes conduction between the poles, reduces the difficulty of using composite fluid collections, and reduces the consumption of traditional foils.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447724A_ABST
    Figure CN119447724A_ABST
Patent Text Reader

Abstract

The invention discloses a composite current collector welding method, which relates to the technical field of current collector welding, and comprises the following operation steps: step 1, reserving a tab area and a non-tab area on a composite current collector, and coating an active material on the non-tab area to obtain a pole piece tab; step 2, punching the pole piece tab to obtain a through hole which is a pole piece tab A; 3, pasting the pole piece tab A on a metal foil by using a conductive adhesive to obtain a pole piece; and 4, laminating the pole pieces, and welding by using an ultrasonic electric welding machine to obtain a finished product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of current collector welding, in particular to a composite current collector welding method. Background Art

[0002] With the continuous development of the battery industry, based on its continuous pursuit of high energy density, more and more companies are investing in the development and application of composite current collectors. Composite current collectors effectively reduce the weight of the battery by reducing the amount of metal used, and on this basis give the battery a certain degree of safety. The application of composite current collectors needs to go through transfer welding first. Currently, transfer welding is mainly achieved through ultrasonic welding. By welding traditional metal foils on the metal layers on both sides, the purpose of conduction on both sides is achieved.

[0003] The existing composite current collector welding solution is mainly ultrasonic roll welding, which achieves conduction by welding three layers of foil roll to roll. Compared with traditional battery technology, it is necessary to introduce an automatic roll welding machine, and because the three layers of foil are controlled separately, the equipment debugging is time-consuming and material-intensive, and the efficiency is not high. However, when the composite current collector is ultrasonically welded, the connectivity of the metal coating between the composite current collectors increases, thereby increasing the internal resistance of the current collector, thereby affecting the conduction of current.

[0004] In order to solve the above problems, the present invention ultrasonically welds the composite current collector by cooperating with the conductive adhesive and the through hole, thereby improving the conductivity and yield rate of the product. Summary of the invention

[0005] The object of the present invention is to provide a composite current collector welding method to solve the problems raised in the prior art.

[0006] To achieve the above object, the present invention provides the following technical solutions: A composite current collector welding method comprises the following steps: Step 1: reserve a tab area and a non-tab area on the composite current collector, and coat the non-tab area with active material to obtain a tab of the pole piece; Step 2: Punch a hole in the pole piece and the pole ear to obtain a through hole, which is the pole piece and the pole ear A; Step 3: Use conductive adhesive to stick the pole piece and the pole ear A on the metal foil to obtain the pole piece; Step 4: After stacking the pole pieces, use an ultrasonic welder to weld them to obtain the finished product.

[0007] More optimally, the thickness of the composite current collector is 8µm; the aperture of the through hole is 1-3mm, and the interval between holes is 5mm; the thickness of the metal foil is 4-15μm; and the thickness of the conductive glue is 0.5-2μm.

[0008] More optimally, when the composite current collector is composite aluminum, the metal foil is aluminum foil, and the active material is a positive electrode active material; when the composite current collector is composite copper, the metal foil is copper foil, and the active material is a negative electrode active material.

[0009] In the scheme, the polymer material for preparing the composite current collector is one or two of polypropylene and polybutylene terephthalate.

[0010] Preferably, the punching method is laser punching or mechanical processing; the welding process conditions are: welding head gas pressure 0.05~0.6MPa, amplitude 5%~80%, welding speed 2~40m / min.

[0011] Preferably, the conductive adhesive is a silver conductive adhesive; the preparation method of the silver conductive adhesive is: adding nano-tin and polyvinyl pyrrolidone to deionized water and mixing them evenly to obtain a mixed solution A for standby use; evenly mixing epoxy resin with a diluent, a curing agent, and a silver composite filler, adding the mixed solution A, continuing to mix for 2 to 3 hours, filtering, and obtaining the silver conductive adhesive.

[0012] More optimally, the raw materials of the silver-based conductive adhesive include the following components: by mass, 0.2-0.3 parts of nano-tin, 0.01-0.012 parts of polyvinyl pyrrolidone, 3-4 parts of epoxy resin, 0.2-0.25 parts of neopentyl glycol diglycidyl ether, 0.7-0.8 parts of silver-based composite filler, and 0.1-0.15 parts of curing agent.

[0013] The more optimized preparation method of the silver composite filler is as follows: ultrasonically disperse graphene oxide in deionized water, heat to 115°C~120°C, adjust the pH to 10~11 with ammonia water, add 1H-imidazole-2-methylamine to react for 8~10 hours, cool to room temperature, filter, wash and dry to obtain modified graphene oxide; 2-ethyl-4-methylimidazole and modified graphene oxide are added to ethanol and ultrasonically mixed, silver carbonate is added and evenly mixed, and the mixture is reacted for 30 to 40 minutes, 14 wt % to 15 wt % ammonia solution is added, the pH value of the reaction system is 9 to 11, the mixture is filtered and dried to obtain a silver-based composite filler.

[0014] More optimally, the mass ratio of the graphene oxide to 1H-imidazole-2-methylamine is 0.1-0.2:1; the raw materials of the silver-based composite filler include the following components: 0.4-0.6 parts of 2-ethyl-4-methylimidazole, 0.1-0.3 parts of modified graphene oxide, and 0.65-0.7 parts of silver carbonate, in parts by mass.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention proposes a welding method by combining conductive adhesive with through-holes, which can reduce the waste of materials in roll welding and can directly weld by ultrasonic welding, making the process simpler and more convenient. The welding method can achieve conduction between pole pieces without transfer welding, which reduces the difficulty of using composite current collectors and reduces the consumption of traditional foils.

[0016] In the scheme, ultrasonic welding connects metal materials by generating heat through the mechanical vibration of high-frequency sound waves, especially at the contact surface. The use of conductive adhesive can avoid excessive overcurrent resistance and can also act as a certain conductive medium to help ultrasonic vibrations better transmit to the welding area. When there is a gap between the welding surfaces, the presence of conductive adhesive can effectively improve the transfer of energy and promote the smooth progress of the welding process. The conductive particles contained in the conductive adhesive can promote current conduction by providing a conductive path, thereby improving the conductivity of the welding point.

[0017] In the scheme, graphene oxide is modified by 1H-imidazole-2-methylamine, and then prepared into a silver-based composite filler with 2-ethyl-4-methylimidazole and silver carbonate; nano-tin, epoxy resin, diluent and silver-based composite filler are then evenly mixed to obtain a silver-based conductive adhesive.

[0018] Among them, silver carbonate has chelated Ag + It coordinates with 2-ethyl-4-methylimidazole and the imidazole nitrogen heterocycle on the modified graphene to form a stable complex, forming a conductive path in the conductive adhesive; and graphene oxide can effectively prevent silver from oxidizing under high temperature conditions, thereby stabilizing the bulk conductive properties of the conductive adhesive. In addition, 2-ethyl-4-methylimidazole and modified graphene play a curing role and are beneficial to enhancing the interface compatibility between the conductive filler and the epoxy resin. Nanotin is a low-melting-point metal. Evenly mixing it with polyvinyl pyrrolidone is beneficial to improving its dispersibility in the epoxy resin, thereby improving the stability of the conductive adhesive under high temperature conditions. Neopentyl glycol diglycidyl ether is used as a diluent to control the viscosity of the system, improve fluidity, and increase wettability. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 A composite current collector for coating positive electrode active materials; Figure 2 It is a schematic diagram of lamination welding; In the figure: 1-composite aluminum ear, 2-through hole, 3-positive electrode active material, 4-aluminum foil, 5-conductive glue. DETAILED DESCRIPTION

[0020] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] In the following specific embodiments, parts are by mass. In this embodiment, it should be noted that the purchase manufacturers of all raw materials involved in the present invention are not subject to any special restrictions, and exemplary examples include: 1H-imidazole-2-methylamine has a CAS number of 53332-80-2, purchased from Shanghai Yuanye Biotechnology Co., Ltd.; graphene oxide has a CAS number of M33420, purchased from Shanghai Mairui Biochemical Technology Co., Ltd.; 2-ethyl-4-methylimidazole has a CAS number of 931-36-2, purchased from Shandong Deke Biotechnology Co., Ltd.; silver carbonate has a CAS number of 931-36-2, purchased from Shandong Deke Biotechnology Co., Ltd. The CAS number is 534-16-7, purchased from Shanghai Yuanye Biotechnology Co., Ltd.; the model of flaky silver powder is 4701086, purchased from Forsman Technology (Beijing) Co., Ltd.; the product number of polyvinyl pyrrolidone is S30268, purchased from Shanghai Yuanye Biotechnology Co., Ltd.; the CAS number of neopentyl glycol diglycidyl ether (diluent) is 17557-23-2, purchased from Hubei Jusheng Technology Co., Ltd.; the epoxy resin is bisphenol A type epoxy resin, the product number is QF6169, purchased from Hubei Qifei Pharmaceutical Chemical Co., Ltd.

[0022] Embodiment 1: A composite current collector welding method; Step 1: reserve a tab area and a non-tab area on the composite current collector, and coat the non-tab area with a positive electrode active material 3 to obtain a tab 1; Among them, the composite current collector is composite aluminum, and its thickness is 8μm; Step 2: Punch a hole in the pole piece and the pole ear 1 to obtain a through hole 2, which is the pole piece and the pole ear A; Among them, the diameter of the through hole is 2mm, and the interval between holes is 5mm; Step 3: Weighing graphene oxide and 1H-imidazole-2-methylamine in a mass ratio of 0.12:1; ultrasonically dispersing the graphene oxide in deionized water, heating to 120° C., adjusting the pH to 11 with ammonia water, adding 1H-imidazole-2-methylamine to react for 8 hours, cooling to room temperature, filtering, washing, and drying to obtain modified graphene oxide; 0.4 parts of 2-ethyl-4-methylimidazole and 0.1 parts of modified graphene oxide were added to ethanol and ultrasonically mixed, 0.65 parts of silver carbonate were added and uniformly mixed, reacted for 30 minutes, 15 wt % of ammonia solution was added, the pH of the reaction system was 10, filtered and dried to obtain a silver-based composite filler; 0.2 parts of nano-tin and 0.01 parts of polyvinyl pyrrolidone were added to deionized water and mixed evenly to obtain a mixed solution A for later use; 3 parts of epoxy resin were mixed evenly with 0.2 parts of neopentyl glycol diglycidyl ether, 0.12 parts of curing agent, and 0.7 parts of silver composite filler, and the mixed solution A was added, and the mixture was mixed for 2 hours, and filtered to obtain a silver conductive adhesive, namely conductive adhesive 5; The electrode tab A is attached to the metal foil 4 using a conductive adhesive 5 to obtain the electrode; The thickness of the aluminum foil 4 is 12 μm, and the thickness of the conductive adhesive 5 is 1 μm; Step 4: After laminating the pole pieces, use an ultrasonic welding machine to weld them to obtain a finished product; Among them, the specific process of ultrasonic welding is as follows: welding head air pressure 0.1MPa, amplitude 20%, and welding speed 5m / min.

[0023] Embodiment 2: A composite current collector welding method; Step 1: reserve a tab area and a non-tab area on the composite current collector, and coat the non-tab area with a positive electrode active material 3 to obtain a tab 1; Among them, the composite current collector is composite aluminum, and its thickness is 8μm; Step 2: Punch a hole in the pole piece and the pole ear 1 to obtain a through hole 2, which is the pole piece and the pole ear A; Among them, the diameter of the through hole is 2mm, and the interval between holes is 5mm; Step 3: Weighing graphene oxide and 1H-imidazole-2-methylamine in a mass ratio of 0.12:1; ultrasonically dispersing the graphene oxide in deionized water, heating to 120° C., adjusting the pH to 11 with ammonia water, adding 1H-imidazole-2-methylamine to react for 8 hours, cooling to room temperature, filtering, washing, and drying to obtain modified graphene oxide; 0.6 parts of 2-ethyl-4-methylimidazole and 0.2 parts of modified graphene oxide were added to ethanol and ultrasonically mixed, 0.7 parts of silver carbonate was added and uniformly mixed, reacted for 30 minutes, 15 wt % of ammonia solution was added, the pH of the reaction system was 10, filtered and dried to obtain a silver-based composite filler; 0.25 parts of nano-tin and 0.012 parts of polyvinyl pyrrolidone were added to deionized water and mixed evenly to obtain a mixed solution A for standby use; 3.5 parts of epoxy resin, 0.2 parts of neopentyl glycol diglycidyl ether, 0.12 parts of curing agent, and 0.74 parts of silver-based composite filler were evenly mixed, and the mixed solution A was added, and the mixture was continued to be mixed for 2 hours, and filtered to obtain a silver-based conductive adhesive, namely conductive adhesive 5; The electrode tab A is attached to the metal foil 4 using a conductive adhesive 5 to obtain the electrode; The thickness of the aluminum foil 4 is 12 μm, and the thickness of the conductive adhesive 5 is 1 μm; Step 4: After laminating the pole pieces, use an ultrasonic welding machine to weld them to obtain a finished product; Among them, the specific process of ultrasonic welding is as follows: welding head air pressure 0.1MPa, amplitude 20%, and welding speed 5m / min.

[0024] Embodiment 3: A composite current collector welding method; Step 1: reserve a tab area and a non-tab area on the composite current collector, and coat the non-tab area with a positive electrode active material 3 to obtain a tab 1; Among them, the composite current collector is composite aluminum, and its thickness is 8μm; Step 2: Punch a hole in the pole piece and the pole ear 1 to obtain a through hole 2, which is the pole piece and the pole ear A; Among them, the diameter of the through hole is 2mm, and the interval between holes is 5mm; Step 3: Weighing graphene oxide and 1H-imidazole-2-methylamine in a mass ratio of 0.12:1; ultrasonically dispersing the graphene oxide in deionized water, heating to 120° C., adjusting the pH to 11 with ammonia water, adding 1H-imidazole-2-methylamine to react for 8 hours, cooling to room temperature, filtering, washing, and drying to obtain modified graphene oxide; 0.6 parts of 2-ethyl-4-methylimidazole and 0.3 parts of modified graphene oxide were added to ethanol and ultrasonically mixed, 0.65-0.7 parts of silver carbonate were added and uniformly mixed, reacted for 30 minutes, 15 wt % of ammonia solution was added, the pH of the reaction system was 10, filtered and dried to obtain a silver composite filler; 0.3 parts of nano-tin and 0.012 parts of polyvinyl pyrrolidone were added to deionized water and mixed evenly to obtain a mixed solution A for standby use; 4 parts of epoxy resin were mixed evenly with 0.25 parts of neopentyl glycol diglycidyl ether, 0.12 parts of curing agent, and 0.8 parts of silver composite filler, and the mixed solution A was added, and the mixture was mixed for 2 hours, and filtered to obtain a silver conductive adhesive, namely conductive adhesive 5; Conductive glue 5 is applied on both sides of the composite aluminum tab 1 of the pole piece A, and aluminum foil 4 corresponding to the size of the composite aluminum tab 1 is attached and cured to obtain a pole piece B; The pole piece tab A is attached to the metal foil 4 using a conductive adhesive 5 to obtain a pole piece stack; The thickness of the aluminum foil 4 is 12 μm, and the thickness of the conductive adhesive 5 is 1 μm. Step 4: After laminating the pole pieces, use an ultrasonic welding machine to weld them to obtain a finished product; Among them, the specific process of ultrasonic welding is as follows: welding head air pressure 0.1MPa, amplitude 20%, and welding speed 5m / min.

[0025] Comparative Example 1 is based on Example 2: no nano-tin is added; Step 1: reserve a tab area and a non-tab area on the composite current collector, and coat the non-tab area with a positive electrode active material 3 to obtain a tab 1; Among them, the composite current collector is composite aluminum, and its thickness is 8μm; Step 2: Punch a hole in the pole piece and the pole ear 1 to obtain a through hole 2, which is the pole piece and the pole ear A; Among them, the diameter of the through hole is 2mm, and the interval between holes is 5mm; Step 3: Weighing graphene oxide and 1H-imidazole-2-methylamine in a mass ratio of 0.12:1; ultrasonically dispersing the graphene oxide in deionized water, heating to 120° C., adjusting the pH to 11 with ammonia water, adding 1H-imidazole-2-methylamine to react for 8 hours, cooling to room temperature, filtering, washing, and drying to obtain modified graphene oxide; 0.6 parts of 2-ethyl-4-methylimidazole and 0.2 parts of modified graphene oxide were added to ethanol and ultrasonically mixed, 0.7 parts of silver carbonate was added and uniformly mixed, reacted for 30 minutes, 15 wt % of ammonia solution was added, the pH of the reaction system was 10, filtered and dried to obtain a silver-based composite filler; 3.5 parts of epoxy resin, 0.2 parts of neopentyl glycol diglycidyl ether, 0.12 parts of curing agent, and 0.74 parts of silver composite filler were uniformly mixed, and filtered to obtain a silver conductive adhesive, namely conductive adhesive 5; The electrode tab A is attached to the metal foil 4 using a conductive adhesive 5 to obtain the electrode; The thickness of the aluminum foil 4 is 12 μm, and the thickness of the conductive adhesive 5 is 1 μm; Step 4: After laminating the pole pieces, use an ultrasonic welding machine to weld them to obtain a finished product; Among them, the specific process of ultrasonic welding is as follows: welding head air pressure 0.1MPa, amplitude 20%, and welding speed 5m / min.

[0026] Comparative Example 2 is based on Example 2: no graphene oxide is added; Step 1: reserve a tab area and a non-tab area on the composite current collector, and coat the non-tab area with a positive electrode active material 3 to obtain a tab 1; Among them, the composite current collector is composite aluminum, and its thickness is 8μm; Step 2: Punch a hole in the pole piece and the pole ear 1 to obtain a through hole 2, which is the pole piece and the pole ear A; Among them, the diameter of the through hole is 2mm, and the interval between holes is 5mm; Step 3: add 0.6 parts of 2-ethyl-4-methylimidazole to ethanol and mix them by ultrasonic, add 0.7 parts of silver carbonate and mix them evenly, react for 30 minutes, add 15 wt % ammonia solution, the pH of the reaction system is 10, filter and dry to obtain a silver composite filler; 0.25 parts of nano-tin and 0.012 parts of polyvinyl pyrrolidone were added to deionized water and mixed evenly to obtain a mixed solution A for standby use; 3.5 parts of epoxy resin, 0.2 parts of neopentyl glycol diglycidyl ether, 0.12 parts of curing agent, and 0.74 parts of silver-based composite filler were evenly mixed, and the mixed solution A was added, and the mixture was continued to be mixed for 2 hours, and filtered to obtain a silver-based conductive adhesive, namely conductive adhesive 5; The electrode tab A is attached to the metal foil 4 using a conductive adhesive 5 to obtain the electrode; The thickness of the aluminum foil 4 is 12 μm, and the thickness of the conductive adhesive 5 is 1 μm; Step 4: After laminating the pole pieces, use an ultrasonic welding machine to weld them to obtain a finished product; Among them, the specific process of ultrasonic welding is as follows: welding head air pressure 0.1MPa, amplitude 20%, and welding speed 5m / min.

[0027] Comparative Example 3 is based on Example 2: the silver composite filler is replaced with flaky silver powder; Step 1: reserve a tab area and a non-tab area on the composite current collector, and coat the non-tab area with a positive electrode active material 3 to obtain a tab 1; Among them, the composite current collector is composite aluminum, and its thickness is 8μm; Step 2: Punch a hole in the pole piece and the pole ear 1 to obtain a through hole 2, which is the pole piece and the pole ear A; Among them, the diameter of the through hole is 2mm, and the interval between holes is 5mm; Step 3: Add 0.25 parts of nano-tin and 0.012 parts of polyvinyl pyrrolidone into deionized water and mix them evenly to obtain a mixed solution A for later use; evenly mix 3.5 parts of epoxy resin, 0.2 parts of neopentyl glycol diglycidyl ether, 0.12 parts of curing agent, and 0.74 parts of flaky silver powder, add the mixed solution A, continue mixing for 2 hours, filter, and obtain a silver-based conductive adhesive, namely conductive adhesive 5; The electrode tab A is attached to the metal foil 4 using a conductive adhesive 5 to obtain the electrode; The thickness of the aluminum foil 4 is 12 μm, and the thickness of the conductive adhesive 5 is 1 μm; Step 4: After laminating the pole pieces, use an ultrasonic welding machine to weld them to obtain a finished product; Among them, the specific process of ultrasonic welding is as follows: welding head air pressure 0.1MPa, amplitude 20%, and welding speed 5m / min.

[0028] Testing experiment: The resistivity (Ω·cm) of the conductive adhesives of Examples 1-3 and Comparative Examples 1-3 was tested; 100 pieces of each of Example 2 and Comparative Examples 1-3 were taken to test the yield of Example 2 and Comparative Examples 1-3; as shown in Tables 1-2.

[0029] Table 1

[0030] Table 2

[0031] Conclusion: It is found from Tables 1 and 2 that the addition of nano-tin has little effect on the resistivity of the conductive adhesive, but its yield rate is reduced; because heat is generated during ultrasonic welding, and the addition of nano-tin can improve the stability of the conductive adhesive under high temperature conditions. Comparative Example 2 is based on Example 2: graphene oxide is not added; because the addition of graphene oxide can reduce the overcurrent resistance, so that the conductive adhesive can help the ultrasonic vibration to be better transmitted to the welding area when used as a conductive medium, thereby improving the welding effect. Comparative Example 3 is based on Example 2: the silver-based composite filler is replaced with flaky silver powder; resulting in a decrease in the dispersibility of the silver powder in the epoxy resin, which leads to a decrease in the resistivity and yield rate.

[0032] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A composite current collector welding method, characterized in that: The steps include: Step 1: a tab region and a non-tab region are reserved on the composite current collector, and an active material (3) is coated on the non-tab region to obtain a tab (1); Step 2: Punch a hole in the pole piece tab (1) to obtain a through hole (2), which is the pole piece tab A; Step 3: Use conductive adhesive (5) to stick the electrode tab A onto the metal foil (4) to obtain the electrode; Step 4: After stacking the pole pieces, use an ultrasonic welder to weld them to obtain the finished product.

2. A composite current collector welding method according to claim 1, characterized in that: The thickness of the composite current collector is 8 μm; the aperture of the through hole (2) is 1 to 3 mm, and the interval between holes is 5 mm; the thickness of the metal foil (4) is 4 to 15 μm; and the thickness of the conductive adhesive (5) is 0.5 to 2 μm.

3. A composite current collector welding method according to claim 1, characterized in that: When the composite current collector is composite aluminum, the metal foil (4) is aluminum foil, and the active material (3) is a positive electrode active material; when the composite current collector is composite copper, the metal foil (4) is copper foil, and the active material (3) is a negative electrode active material.

4. A composite current collector welding method according to claim 1, characterized in that: The punching method is laser punching or mechanical processing; the welding process conditions are: welding head air pressure 0.05~0.6MPa, amplitude 5%~80%, welding speed 2~40m / min.

5. A composite current collector welding method according to claim 1, characterized in that: The conductive adhesive is a silver-based conductive adhesive. The preparation method of the silver-based conductive adhesive is as follows: nano-tin and polyvinyl pyrrolidone are added to deionized water and mixed uniformly to obtain a mixed solution A for standby use; epoxy resin is uniformly mixed with a diluent, a curing agent, and a silver-based composite filler, and the mixed solution A is added, and the mixture is continuously mixed for 2 to 3 hours, and filtered to obtain the silver-based conductive adhesive.

6. A composite current collector welding method according to claim 5, characterized in that: The raw materials of the silver-based conductive adhesive include the following components: by mass, 0.2-0.3 parts of nano-tin, 0.01-0.012 parts of polyvinyl pyrrolidone, 3-4 parts of epoxy resin, 0.2-0.25 parts of neopentyl glycol diglycidyl ether, 0.7-0.8 parts of silver-based composite filler, and 0.1-0.15 parts of curing agent.

7. A composite current collector welding method according to claim 5, characterized in that: The preparation method of the silver-based composite filler is as follows: ultrasonically dispersing graphene oxide in deionized water, heating to 115°C-120°C, adjusting the pH to 10-11 with ammonia water, adding 1H-imidazole-2-methylamine to react for 8-10 hours, cooling to room temperature, filtering, washing, and drying to obtain modified graphene oxide; 2-ethyl-4-methylimidazole and modified graphene oxide are added to ethanol and ultrasonically mixed, silver carbonate is added and evenly mixed, and the mixture is reacted for 30 to 40 minutes, 14 wt % to 15 wt % ammonia solution is added, the pH value of the reaction system is 9 to 11, the mixture is filtered and dried to obtain a silver-based composite filler.

8. A welding method for a composite current collector according to claim 7, characterized in that: The mass ratio of the graphene oxide to 1H-imidazole-2-methylamine is 0.1-0.2:1; the raw materials of the silver-based composite filler include the following components: 0.4-0.6 parts of 2-ethyl-4-methylimidazole, 0.1-0.3 parts of modified graphene oxide, and 0.65-0.7 parts of silver carbonate, calculated by mass.